1992
DOI: 10.1530/jrf.0.0950175
|View full text |Cite
|
Sign up to set email alerts
|

Effects of active immunization against a synthetic peptide sequence of the inhibin  -subunit on plasma gonadotrophin concentrations, ovulation rate and lambing rate in ewes

Abstract: Thirty adult Mule (Blue-faced Leicester x Swaledale) ewes were actively immunized against a synthetically produced peptide corresponding to the N-terminus of the alpha-subunit of bovine inhibin conjugated to tuberculin purified protein derivative (PPD). Primary immunization in the late anoestrous period was followed by two booster injections at 5 week intervals. Control groups were either not immunized (n = 15) or received PPD only (n = 15). Ten days after the second booster, oestrus was synchronized using pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
19
0
1

Year Published

1994
1994
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 13 publications
5
19
0
1
Order By: Relevance
“…Taken together, the findings may indicate that it is very difficult to induce superovulation in guinea pigs by temporarily increasing FSH. Passive immunization against inhibin increases FSH secretion in rats [10,30], hamsters [9], cows [7,8] and ewes [31][32][33] as expected. In contrast, in the present study, passive immunizations against inhibin failed to cause an apparent in increase in the plasma FSH level before ovulation.…”
Section: Discussionsupporting
confidence: 59%
“…Taken together, the findings may indicate that it is very difficult to induce superovulation in guinea pigs by temporarily increasing FSH. Passive immunization against inhibin increases FSH secretion in rats [10,30], hamsters [9], cows [7,8] and ewes [31][32][33] as expected. In contrast, in the present study, passive immunizations against inhibin failed to cause an apparent in increase in the plasma FSH level before ovulation.…”
Section: Discussionsupporting
confidence: 59%
“…About 1 year earlier, six of the ewes had been actively immunized against a synthetic peptide corresponding to the amino terminal region (amino acids 1-29) of the mature C subunit of bovine inhibin conjugated to tuberculin purified protein derivative (PPD) as described elsewhere (Wrathall et al 1990(Wrathall et al , 1992. At the same time four of the ewes were actively immunized against PPD alone to serve as carrierimmunized controls.…”
Section: Animalsmentioning
confidence: 99%
“…The existence of such ovarian compensatory mechanisms is also indicated by two studies carried out in this laboratory (Knight et al 1991b, Fray et al 1994) in which we failed to detect raised FSH levels in groups of long-term (>6-month) actively immunized ewes. Previously, the same ewes had shown raised FSH levels during their initial active immunization regimen (see Wrathall et al 1990Wrathall et al , 1992. Such inconsistencies in the FSH response to long-term inhibin immunoneutralization indicate that inhibin antibodies may have additional direct stimulatory effects on follicle development that are independent of changes in FSH secretion.…”
Section: Introductionmentioning
confidence: 99%
“…Dev. 48: [599][600][601][602][603][604][605] 2002) t is reported that immunoneutralization of inhibin to induce superovulation provides an alternative to current follicle stimulating hormone (FSH) or equine chorionic gonadotropin (eCG) t r eat m en t pr o t o c o ls fo r t h e pr o d uc t i o n o f transferable embryos in mammals [1][2][3][4][5][6][7][8]. Several studies have shown that active immunization of heifers against inhibin α-subunit [9-13] and passive…”
mentioning
confidence: 99%